2014
DOI: 10.1038/nnano.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Selective transport control on molecular velcro made from intrinsically disordered proteins

Abstract: The selectivity and speed of many biological transport processes transpire from a 'reduction of dimensionality' that confines diffusion to one or two dimensions instead of three. This behaviour remains highly sought after on polymeric surfaces as a means to expedite diffusional search processes in molecular engineered systems. Here, we have reconstituted the two-dimensional diffusion of colloidal particles on a molecular brush surface. The surface is composed of phenylalanine-glycine nucleoporins (FG Nups)--in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 31 publications
4
46
3
Order By: Relevance
“…Kapprobes) on FG layers in the presence of soluble Kapb1. 52 There, we found that the Kap-probes remained stuck to the FG layer (i.e., slow) at low Kapb1 concentrations but exhibited unhindered 2-dimensional diffusion on the layer (i.e., fast) at physiological Kapb1 concentrations. In contrast, non-specific control probes exhibited 3-dimensional diffusion that only transiently impinged the FG layer but did not bind.…”
Section: Biophysical Evidence Of Kapcentric Controlmentioning
confidence: 67%
See 1 more Smart Citation
“…Kapprobes) on FG layers in the presence of soluble Kapb1. 52 There, we found that the Kap-probes remained stuck to the FG layer (i.e., slow) at low Kapb1 concentrations but exhibited unhindered 2-dimensional diffusion on the layer (i.e., fast) at physiological Kapb1 concentrations. In contrast, non-specific control probes exhibited 3-dimensional diffusion that only transiently impinged the FG layer but did not bind.…”
Section: Biophysical Evidence Of Kapcentric Controlmentioning
confidence: 67%
“…In comparison, weakly bound Kaps might exhibit a 2-dimensional random walk along the luminal "surface" of the translocation corridor owing to the dirty velcro effect with brief excursions into the luminal space. 52 This could in fact expedite transport because the temporal requirement of a 2-dimensional search process for finding the exit of a spatially constrained pore can be considerably less than in 3 dimensions. According to ROD theory, 53,55 the mean diffusion time t for a particle (assuming a constant diffusion coefficient) is related to t 3D » L=b in three dimensions;…”
Section: Implications Of Kap-centric Controlmentioning
confidence: 99%
“…[293][294][295][296][298][299][300][301][302][303][304][305][306] A key point is that the interaction between the nanoparticle ligands and the target receptors must be both selective and weak, so that, in analogy to Velcro s , the particle only binds to surfaces that have a high concentration of receptors. 307,308 Currently, coatings targeting cancers are identified mainly through large trial and error screenings with limited help from computational modelling, and without specific design to control the binding affinity. The key to the realization of velcro-like particles is in the design of both the binding strength and specificity of the ligand-receptor bonds 293,307 as well as the control over the geometrical distribution of the ligands on the surface of the nanoparticles.…”
Section: Biopolymers and Proteinsmentioning
confidence: 99%
“…307,308 Currently, coatings targeting cancers are identified mainly through large trial and error screenings with limited help from computational modelling, and without specific design to control the binding affinity. The key to the realization of velcro-like particles is in the design of both the binding strength and specificity of the ligand-receptor bonds 293,307 as well as the control over the geometrical distribution of the ligands on the surface of the nanoparticles. Proteins are an optimal choice as ligands since they offer excellent control over binding selectivity and can be chosen so as to minimize the interference with normal cell function.…”
Section: Biopolymers and Proteinsmentioning
confidence: 99%
“…[60] FG Nup-functionalized surfaces have also been shown to reconstitute selective transport in two dimensions. [61] Accordingly, this presents a molecular logistics paradigm for regulating transport and communication between artificial organelles, i.e. so-called 'artificial nuclei', …”
Section: To Wards 'Artificial Nuclei'mentioning
confidence: 99%